Role of Nurse to Continue Developmental Care for Premature Infants - Phianching, Kulwara; Klankhajhon, Sirikanok (NU Journal of Nursing and Health Sciences, 2022)
Premature newborns face with a critical condition that need to get as a critical care. It focuses on holistic and continuing care to gain growth and development of preterm infants including and also reducing risks of complications, mortality and morbidity, and promote long term quality of life. Preterm newborn care should concern the different between outside and inside mother’s womb. Nurses play significant roles to providing nursing care that aware of developmental care for preterm infant. The core concepts of developmental care for preterm newborns are as follows: 1) Safeguarding sleep 2) Minimizing stress and pain 3) Partnering with families 4) Optimizing nutrition, protecting skin, and positioning and handling 5) Creating healing environment. These concepts are a standard care to improve the quality of life for preterm newborn which take place from the delivery room, intensive care unit and at home as a holistic and continue care.